ACCOUNTING OF BEARER PLANTS IN THE SCOPE OF IAS 16: TANGIBLE FIXED ASSETS STANDARD AND AN APPLICATION IN AN ALMOND ORCHARD (Third Sector Social Economic Review, 2021)
Although the importance of agriculture for the global economy seems generally acknowledged, the debate about financial reporting and accounting processes for the sector still continues. In our country, IAS 41: Agricultural Activities standard, which is the first standard for the regulation of accounting transactions related to agricultural activities, entered into force in 2006. Bearer plants until 2014 have been accounted for under this standard. However, with the communiques numbered 30 and 31 published by the Public Oversight Accounting and Auditing Standards Authority (KGK) on 12.11.2014, bearer plants were excluded from the scope of IAS 41 standard and included in the scope of IAS 16: Tangible Fixed Assets Standard. The purpose of this study is to determine the principles for the accounting of bearer plants within the scope of IAS 16 standard and to explain the regulations in the standard regarding the valuation during the reporting periods. In the study, the case study method was used by using the data from an almond orchard in Mersin. Within the scope of IAS 16, the initial accounting, valuation and depreciation records of the business subject to analysis in the reporting periods are shown in detail. In addition, the study shows how the differences in valuation models affect the financial statements. The depreciation calculation is made according to the standard rather than the mandatory provisions of the tax legislation to be implemented in Turkey. With the inclusion of the bearer plants into the fixed asset group, it has been concluded that they will be subject to many applications such as their evaluation within the scope of IAS 16, accounting and valuation principles, and that financial statements will be prepared more accurately, fairly and transparently.
Keywords: Almond Cultivation; Bearer Plants; IAS 16: Tangible Fixed Assets Standard; IAS 41: Agricultural Activities Standard.